Perioperative complications and length of stay in patients with diabetes mellitus after aseptic revision total shoulder arthroplasty - Arman Kishan; Sarah I. Goldfarb; Jake DePalo; Henry Maxwell Fox; Ansh Kishan; Umasuthan Srikumaran (Journal of Orthopaedic Reports)
Background: Total shoulder arthroplasty (TSA) is increasingly performed, but complications and revisions are rising concerns, especially in the presence of comorbidities such as diabetes mellitus (DM). Our study aimed to assess the association between DM and perioperative complications and length of hospital stay after aseptic revision TSA, which has been underexplored. Methods: Using the National Surgical Quality Improvement Program (NSQIP) database, we analyzed 1979 patients undergoing revision TSA from 2006 to 2021. Patients were categorized as with DM (n = 404) or without DM (n = 1575). We examined patient demographics, comorbidities, and surgical characteristics. Multivariate logistic regression was used to identify risk factors for major complications and prolonged hospital stays. Results: Patients with DM showed similar rates of major and minor complications and hospital stays compared to those without DM. Hypertension emerged as a significant risk factor for major complications (odds ratio [OR] 4.0, 95 % confidence interval [CI] 1.3, 17.1), whereas American Society of Anesthesiologists classification >2 (OR 3.6, 95 % CI 1.4, 12.6) and preoperative hematocrit <35 % (OR 4.3, 95 % CI 2.1, 8.6) were associated with prolonged hospital stays. Multivariate analysis did not find DM to be an independent predictor of prolonged hospital stays. Discussion: In patients undergoing aseptic revision TSA, 30-day complication rates and lengths of hospital stays did not differ significantly between patients with and without DM. These findings challenge previous assumptions about DM's impact on TSA revisions. The present study emphasizes the importance of individualized risk assessment, focusing on comorbidities such as hypertension and anemia, which appear to play a more critical role in outcomes. Further research is needed to explore the heterogeneity within the diabetic population and to refine bundled-care models to optimize risk stratification and resource allocation in TSA revisions.